Twenty Five Years Of Human Assisted Reproduction In Peru - Llerena Cano, Guillermo (2015)
In Peru, the first procedures of assisted human reproduction (AHR) were performed in 1989 by the PRANOR Group. Twenty-five years later, in 2014, the sequence of development of this technology is reviewed, identifying globally the top developmental milestones.In this paper, two periods of technological development of the RHA in Peru are set, the first between 1989 and 1998, and the second between 1999 and 2014; defining concepts, techniques and specific terminology for ease of understanding.